Increasing Safety Capacity at Special Education Schools in Semarang City - Evi Widowati; Ummi Nur Laila Sulistyani; Anik Setyo Wahyuningsih; Lutfi Muzaqi; Risa Anggita Putri (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
Special Education Schools (SLB) are formal educational institutions that provide services for students with special needs. Until now, SLB still faces significant challenges related to safety in the school environment. To overcome these challenges, mentoring activities are needed to increase safety capacity for teachers, staff and security officers at the Semarang City State SLB. This community service activity uses a participatory approach and is carried out in three stages: preparation, implementation and evaluation. Initial observations showed various problems such as inappropriate evacuation routes, invisible meeting points and expired fire extinguishers. Through mentoring and training activities that combine lecture, discussion and practice methods, participants experienced a 37% increase in knowledge. The evaluation results showed increased participants' knowledge and awareness regarding the importance of implementing safety in schools. This program is expected to be a model for strengthening safety capacity in SLB and encouraging a safe and inclusive learning environment.